Accounting Students’ Perspectives on Fraud and Forensic Topics in the Accounting Curriculum: A Comparison with Professionals - Nouri, Hossein (Journal of Knowledge Management Practice, 2025)
Forensic accounting is a growing field, especially given the increasing threat of fraud in businesses today. This study examines accounting students’ perspectives on fraud and forensic topics that they believe should be included in the accounting curriculum. This study also compares students’ perspectives with those of professionals. A survey of sophomores and seniors at a liberal arts undergraduate college in the Northeast United States was conducted. It asked students about the importance of certain qualities they perceive a forensic accountant should possess and topics they should be familiar with. In addition, students’ responses were compared with the results of Daniels et al.’s (2013) study regarding professionals’ responses. The results showed that sophomores and seniors significantly differed in their perceptions of internal control and fraud risk factors. In addition, students and professionals had significantly different perceptions of what the most critical forensic accounting topics should be included in the accounting curriculum. These differences are presented and discussed in the paper.